Assessing the relation between systemic lupus erythematosus and metabolic syndrome in Syria: a cross-sectional study - Noura Mallouhi; Ahmad Nabil Alhouri; Naram Khalayli; Hasan Nabil Alhouri; Mayssoun Kudsi; Younes Kabalan (BMC Rheumatology)
Abstract Background Systemic Lupus Erythematosus (SLE) affects all organ systems. As a result, fat intake and sedentary life are evident in the modern world. The prevalence of metabolic syndrome, with its components, increased, leading to increased mortality. We aimed to investigate the prevalence of metabolic syndrome in SLE and its relationship with disease activity. Methods A cross-sectional study was conducted on 70 SLE patients at Al Mouwasat University Hospitals in Damascus, Syria, between November 2021 and November 2022. The patients were divided into two groups based on the presence or absence of metabolic syndrome. The SLE Disease Activity Index (SLEDAI) was assessed in each group and compared with different disease parameters. Results Out of the 70 patients, 65 were females. The mean age was 32.19 ± 7.15 years, and the mean disease duration was 4.4 ± 2.96 years. Metabolic syndrome was found in 32 patients (45.7%). Metabolic syndrome in SLE patients was associated with a higher disease activity index, older age, delayed age at first diagnosis, longer disease duration, higher frequency of renal involvement, and use of cyclophosphamide. Conclusion Our study highlights the importance of evaluating and treating metabolic syndrome and its components in patients with SLE, as it may play a role in controlling disease activity. We recommend conducting larger studies in the future to overcome the limitations of this research, such as including a larger number of patients, conducting multicenter studies to generalize the results, and including a healthy control group.